Menemukan Harmoni Alam Dan Manusia: Kajian Filsafat Lingkungan Hidup A. Sonny Keraf Atas Laudato Si’ Artikel 66-69 Dan Relevansinya Bagi Bangsa Indonesia - Sekundus Septo Pigang Ton; Mathias Jebaru Adon; FX. Eko Armada Riyanto (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The focus in writing this article is Finding Harmony between Nature and Humans: A Study of Environmental Philosophy. Sonny Keraf on Laudato Si Articles 66-69 and its Relevance for the Indonesian Nation. Nature as a living environment is a place for humans to live. In addition to shelter, humans also take products from it for the needs of life. Along with the progress of the times, human needs continue to grow and humans continue to take products from nature. But lately, the destruction of nature often occurs because of the actions of humans who also exploit it excessively. The purpose of writing this article is to examine Sonny Keraf's environmental philosophy on Laudato Si art 66-69, to find the harmonization of nature and humans. The findings of this research are to restore the harmonization of humans and nature, as intelligent beings and part of nature, humans need to preserve and care for the environment as they care for themselves. Destroying the universe means destroying oneself, because humans live and depend on nature, demanding the need for sustainable sustainability and awareness of dependence on nature. The method used in this research is a literature review with descriptive qualitative.